Bibliometric analysis regarding academic literature, on creative industry project costing methodologies - Quiceno-Opina, Johan S. (2023)
The aim of this research is to analyze the advances in relation to the costing of projects of the creative economy, from a bibliometric analysis of the orange, creative and cultural economy, where through searches carried out in databases and tools of Research determines the relevance of these concepts, in the economic field and especially in the research world. The problem evidenced lies in the lack of evaluation systems oriented towards the costs of the creative and cultural industry. Regarding this research, its approach is quantitative and exploratory. The investigations carried out on the object of study are analyzed, contributing in the definition of concepts and the correlation in each of the works, with the idea of ​​knowing and contrasting the perspectives of the investigations to carry out a costing methodology for creative projects In the city of medellin.